1996
DOI: 10.1021/jm950475e
|View full text |Cite
|
Sign up to set email alerts
|

Drug Delivery Systems:  Water Soluble Taxol 2‘-Poly(ethylene glycol) Ester ProdrugsDesign and in Vivo Effectiveness

Abstract: Water soluble 2'-taxol poly(ethylene glycol) (PEG) esters have been synthesized and shown to function in vitro as prodrugs. However, in vivo experiments clearly establish that in order for these prodrugs to behave in a predictable fashion, the molecular weight of PEG must be of such magnitude so as to maintain a t1/2(circulation) > t1/2(hydrolysis). When PEG derivatives of molecular weight approximately 40 kDa were employed with paclitaxel, ca. 4% by weight of paclitaxel was carried by the water soluble prodru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
151
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(162 citation statements)
references
References 35 publications
10
151
0
Order By: Relevance
“…335 The in vitro stability of the different PEG-PTX conjugates was studied evaluating by HPLC the release of PTX, after incubation at 37°C in buffer at various pH values (5.6, 7.4 and 9) or in serum; the results are shown in Table 1. As previously reported by Greenwald (Greenwald et al, 1996), we also observed that the half-life of the conjugates did not depend on the PEG's molecular weight.…”
Section: Water Solubilty and In Vitro Stability Of Peg-ptx Prodrugssupporting
confidence: 89%
See 3 more Smart Citations
“…335 The in vitro stability of the different PEG-PTX conjugates was studied evaluating by HPLC the release of PTX, after incubation at 37°C in buffer at various pH values (5.6, 7.4 and 9) or in serum; the results are shown in Table 1. As previously reported by Greenwald (Greenwald et al, 1996), we also observed that the half-life of the conjugates did not depend on the PEG's molecular weight.…”
Section: Water Solubilty and In Vitro Stability Of Peg-ptx Prodrugssupporting
confidence: 89%
“…The 20 kDa PEG-PTX conjugates showed a decrease in solubility values (150 and 180 mg/mL for mono-and di-substituted, respectively). A similar behavior was also observed for a reported series of PEG-PTX prodrugs, in which the water solubility decreased with the increasing of the polymer's molecular weight (Greenwald et al, 1996). 335 The in vitro stability of the different PEG-PTX conjugates was studied evaluating by HPLC the release of PTX, after incubation at 37°C in buffer at various pH values (5.6, 7.4 and 9) or in serum; the results are shown in Table 1.…”
Section: Water Solubilty and In Vitro Stability Of Peg-ptx Prodrugssupporting
confidence: 74%
See 2 more Smart Citations
“…After 0.5 h, dicyclohexylcarbodiimide (DCC, 5 mg, 0.023 mmol) was added to the reaction, with continued stirring at room temperature for 12 h. The solvent was evaporated, and the crude product was purified three times by recrystallization using methanol/ ether ( The integration of the protons in the aromatic moiety when attached to the high molecular weight PEG does not give accurate peak heights in contrast to other protons in NMR, as reported elsewhere (23). Electrospray mass spectra of the product revealed an inverted U shape mass spectral pattern with an increment of 44 (a characteristic of PEG-based molecules) spanning between molecular weights 2922 and 3450.…”
Section: Chemicals and Generalmentioning
confidence: 99%